2018
DOI: 10.1111/ctr.13311
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and costs of once‐daily and twice‐daily tacrolimus formulations in de novo kidney transplantation

Abstract: The use of once-daily tacrolimus in de novo kidney transplantation is increasingly common. Therefore, we were interested in bioavailability aspects of novel once-daily tacrolimus (LCPT, Envarsus) and once-daily tacrolimus extended-release formulation (ER-Tac, Advagraf) compared with twice-daily immediate-release tacrolimus (IR-Tac, Prograf). Furthermore, we calculated the costs. Kidney allograft recipients on tacrolimus-based immunosuppression within 2 clinical trials were included in a single-center analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 13 publications
7
18
0
1
Order By: Relevance
“…PR‐Tac is more costly in Spain, and savings after conversion to LCP‐Tac were of 1,927 €/year, a 63% reduction. Reductions in costs after conversion to LCP‐Tac have been observed in other studies in the context of kidney or liver transplantation …”
Section: Discussionsupporting
confidence: 73%
“…PR‐Tac is more costly in Spain, and savings after conversion to LCP‐Tac were of 1,927 €/year, a 63% reduction. Reductions in costs after conversion to LCP‐Tac have been observed in other studies in the context of kidney or liver transplantation …”
Section: Discussionsupporting
confidence: 73%
“…Additionally, target therapeutic range of Tac can be diff erent according to transplantation center. In the study of Gleder et al data were gained from two prospective randomized multicenter trials (ClinicalTrials.gov: NCT01187953 and NCT01683331), which had diff erent target range of Tac: (1) 6-11 ng/mL for the fi rst 30 days and 4-11 ng/ mL, aft erwards and (2) 8-12 ng/mL for the fi rst 90 days, then 5-8 ng/mL [14]. In the Symphony study, target levels were even lower, between 3 and 7 ng/mL, and demonstrated lower rates of acute rejection and improved graft function as well [15].…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in Europe have, however, demonstrated a cost-benefit for LCPT due to lower dosing requirements. 31,36 Adherence, as assessed by validated questionnaires, may also be improved with once-daily dosing based on two studies of transplant recipients converted from IR-TAC to XL-TAC. 37,38 As of January 2020, patient assistance remains available through the drug manufacturer of LCPT for qualifying patients in the United States.…”
Section: Extended-release Tacrolimus Efficacymentioning
confidence: 99%